2008
DOI: 10.2320/matertrans.mra2008116
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ferroelectric Na<I><SUB>x</SUB></I>K<SUB>1&minus;<I>x</I></SUB>NbO<SUB>3</SUB> System Films Prepared by Pulsed Laser Deposition

Abstract: Ferroelectric Na x K 1Àx NbO 3 (NKN) films were prepared on quartz and Pt/SrTiO 3 (100) substrates by pulsed laser deposition. The effects of composition and preparation conditions on the crystal structure and ferroelectricity of the NKN films were investigated by changing the Na content (x), substrate temperature (T sub ), oxygen partial pressure (P O2 ), target-to-substrate distance (D t-s ) and laser energy density (E L ). The permittivity values of the NKN films were 390 to 520 at room temperature and 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Recently, KNN‐based thin films have received increasing attention because its bulk counterpart has good piezoelectric properties as a promising lead‐free system. Previously, pulsed laser deposition and magnetron sputtering had been used to fabricate KNN‐based thin films . Although sol–gel method is regarded as a more facile process for thin films fabrication, which has been successfully applied for the fabrication of PZT‐based thin films on various substrates, it met difficulties when used for the case of KNN thin films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, KNN‐based thin films have received increasing attention because its bulk counterpart has good piezoelectric properties as a promising lead‐free system. Previously, pulsed laser deposition and magnetron sputtering had been used to fabricate KNN‐based thin films . Although sol–gel method is regarded as a more facile process for thin films fabrication, which has been successfully applied for the fabrication of PZT‐based thin films on various substrates, it met difficulties when used for the case of KNN thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, pulsed laser deposition and magnetron sputtering had been used to fabricate KNN-based thin films. [9][10][11][12][13] Although sol-gel method is regarded as a more facile process for thin films fabrication, which has been successfully applied for the fabrication of PZT-based thin films on various substrates, 14,15 it met difficulties when used for the case of KNN thin films. Nevertheless, most of those problems have been resolved by the studies to date.…”
Section: Introductionmentioning
confidence: 99%
“…Above all, the pulsed laser deposition has been widely applied for preparation of many kinds of thin films due to several advantages, 1) stoichiometric transfer of compositions from source to film, 2) growth from a high energy beam resulting in high crystallinity, and 3) inherent simplicity for the growth of multilayered structures. However, very few studies on KNN thin films with various compositions have been reported [21].…”
Section: Effect Of A-site Excess On the Piezoelectric Propertiesmentioning
confidence: 99%
“…Besides, Lai et al. studied the effects of K/Na ratio and preparation conditions on the crystal structure and ferroelectricity of KNN films, and the maximum remnant polarization ( P r ) of 8.2 µC cm −2 was obtained at K/Na ratio close to 1 . Additionally, optimal amounts of excess K and Na were found to be 20 mol% to form high‐quality single‐phase Li + , Ta 5+ , and Sb 5+ co‐doped KNN‐based films .…”
Section: Synthetic Techniquesmentioning
confidence: 99%